(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Hardini J, Wirayudha IGB, Rosyidi A, Rita NMA, Mawanti I, Kalih LATTWS, Joni M, Sudaryanto FX. 2023. The carrying capacity of Nusa Penida Island, Bali, Indonesia for Bali myna (Leucopsar rothschildi Stresemann, 1912). Biodiversitas 24: 3462-3470. This study is to analyze the carrying capacity of Nusa Penida Island on the existence of Bali myna (Leucopsar rothschildi Stresemann, 1912), because the population is increasing. Bali myna counting method: (i) Counting Bali myna on the tree where she sleeps. (ii) Counting Bali myna at the time of doing daily activities. Bali myna population in 2021, Ped Village 58 birds, and Toyapakeh Village 4 birds. In 2022, Bali myna in Ped Village had 102 birds, and in Toyapakeh Village 6 birds. On Nusa Penida Island, food sources of fruits and insects are abundant. There is enough nest box or tree hole to make a nest. Bali myna nest nuisance animals are bee honey (Trigona itama, Cockerel 1918 and ant (Ochetellus glaber (Mayr, 1862)), while predators are tokay gecko (Gekko gecko (Linnaeus 1758)), and water monitor (Varanus salvator Laurenti 1768). It is suspected that some Bali myna moved from Ped Village to Toyapakeh Village due to a large number of nesting disturbing animals in Ped Village. Until now, the people of Nusa Penida Island still carry out awig-awig (customary law) to protect Bali myna. From this research, it is known that the carrying capacity of Nusa Penida Island for Bali myna. The move of Bali myna from Ped Village to Toyapakeh Village is not due to a lack of carrying capacity but because of the presence of Bali myna nuisance animals.